Technology and the Intelligence Community Challenges and Advances for the 21st Century (Advanced Sciences and Technologies for Security Applications,, 2018)
This volume examines the role of technology in gathering, assimilating and utilizing intelligence information through the ages. Pushing the boundaries of existing works, the articles contained here take a broad view of the use and implementation of technology and intelligence procedures during the cold war era and the space race, the September 2011 attacks, and more recent cyber operations. It looks at the development of different technologies, procedural implications thereof, and the underlying legal and ethical implications. The findings are then used to explore the future trends in technology including cyber operations, big data, open source intelligence, smart cities, and augmented reality. Starting from the core aspects of technical capabilities the articles dig deeper, exploring the hard and soft infrastructure of intelligence gathering procedures and focusing on the human and bureaucratic procedures involved therein. Technology and innovation have played an important role in determining the course of development of the intelligence community. Intelligence gathering for national security, however, is not limited only to the thread of technical capabilities but is a complex fabric of organizational structures, systemic undercurrents, and the role of personnel in key positions of decision making. The book's findings and conclusions encompass not just temporal variation but also cut across a diverse set of issue areas. This compilation is uniquely placed in the interdisciplinary space combining the lessons from key cases in the past to current developments and implementation of technology options.